دراسة التباينات الوراثية عند نبات القبّار Capparis spinosa المنتشر في محافظتي حلب واللاذقية باستخدام تقانة الــAFLP - يوسف, عزيزة إبراهيم; بركات, عبد اللة; زريقة, ديمة علي (Latakia University Journal -Biological Sciences Series, 2014)
جُمعت عينات من نبات القبّارCapparis spinosa من(6) مناطق توزعت في محافظتي حلب واللاذقية. تمت دراسة التباينات باستخدام تقانة الـ AFLPبهدف تحديد الهوية الوراثية للطرز المدروسة باستخدام (3) بادئات أظهرت مكاثرة للـDNA ، وحُسب معامل الاختلاف ومعامل التنوّع الوراثي، وأنشئت شجرة القرابة الوراثية، وأُجري تحليل المكونات الأساسية (A.C.P.)، وحُسبت F– الإحصائية، فأظهرت هذه الدراسة النتائج التالية: - تأكيد وجود عدد معين من الألليلات (الحزم) التخصصية أو المميزة Discriminateخاصة بكل محافظة، - دلّ هذا على وجود عزل وراثي وتكاثري محدد وعائق للتدفق المورثي gene flow بين المحافظتين. - تميّزت اللاذقية بمعدّل تغايرية (0.486) أعلى بقليل من حلب (0.481)، و متوسط معامل التنوّع الوراثي على مستوى البادئات والأفراد (0.677) في حلب أعلى بقليل من اللاذقية (0.653)، ومستوى المجتمعات المختلفة متقاربة جدا" (0.759) في حلب (0.760 ) في اللاذقية, يُفسّر ذلك وفق ظاهرتي الألليلات الصامتة والتخصصيّة التي تُعزى لحدوث الطفرة بالحذف، وأيضاً لتأثيرات اصطفائية مختلفة ولنظم التكاثر في المحافظتين. - أكبر قيمة للبعد الوراثي في حلب(0.381) بين (الضاحية و الشيخ سعيد)، وأكبر قيمة للبعد الوراثي في اللاذقية (0.38) بين (العمرونية و جبلة)، بينما أكبر قيمة تشابه (0.637) بين (الشيخ سعيد و تركمان بارح) في حلب، و (0.675) بين (وطى ديرزينون و جبلة) في اللاذقية، وتباين متدرج بين هذه القيم المحسوبة. - أظهرت دراسة F- الإحصائية تأثير عامل القرابة في بعض المجتمعات وبرز ذلك أكثر أهمية وأكبر نسبياً في حلب منه في اللاذقية, يدّل ذلك على أن نظام التكاثر أكثر انغلاقاً في حلب و يُعزى للتكاثر عن طريق الجوار أو التلقيح الذاتي، وهذا ما أظهر تباينا" وراثيا عالياً بين مجتمعاتها بالمقارنة مع مجتمعات اللاذقية. - سمحت هذه الدراسة بتحديد بادئات يمكن استخدامها كمؤشرات جزيئية في برامج تحسين القبّار كنبات طبي وغذائي, وأظهرت هذه التقانة كفاءة عالية في دراسة علاقات القرابة بين المجتمعات في المحافظتين. Samples of Capparis spinosa plant were collected from 6 sites in Aleppo and Lattakia provinces. The genetic variations were studied using the AFLP technique in order to determine the genotypes of the studied types using 3 primers, which showed amplification. Statistical analyses were conducted using the dissimilarity coefficient and genetic diversity coefficient. The A.C.P. and the statistical -F were calculated, and the similarity dendrogram was constructed. The results showed the following: The presence of a certain number of specific alleles (descriminates) for each province. The presence of genetic and reproductive isolation deterrent to gene flow between the two provinces. The heterozygoty average was a little higher in Lattakia (0.486) than in Aleppo (0.481). The mean of genetic diversity coefficient of primers and individuals was a little higher in Aleppo (0.677) than in Lattakia (0.653). The population mean was very close: (0.759) in Aleppo and (0.760) in Lattakia. This may be explained on the basis of silent and specific alleles due to deletion mutations, different selective effects as well as the reproduction system in the two cities. The greatest genetic distance in Aleppo was (0.381) noted between (Al Dahea and Al Shekh saaed), and in Lattakia (0.38) noted between (Al Amroniah and Jabla). However, the greatest genetic similarity in Aleppo was (0.637) noted between (Al Shekh Saaed and Turkman Bareh), and in Lattakia (0.675) noted between (Wata Deirzenon and Jabla). The variation between these values was graduated. The study of statistical –F showed the effect of the similarity factor in some populations. This was more significant in Aleppo than in Lattakia, which indicates that the reproduction system is more closed in Aleppo, and this refers as well to inbreeding or self pollination which showed high genetic variations in these populations when compared with Lattakia. The results of this study helped in determining primers that can be used as molecular markers in a breeding program for Capparis spinosa as a medicinal plant. This technique showed high efficiency in studying the similarity relationships between these two cities.